2021
DOI: 10.1039/d0bm01838d
|View full text |Cite
|
Sign up to set email alerts
|

(r)HDL in theranostics: how do we apply HDL's biology for precision medicine in atherosclerosis management?

Abstract: (r)HDL therapeutics has progressed a long way but has yet to produce fruitful results. Based on what has been learned and on the most innovative perspectives, a new generation of “smart” rHDL is emerging as an alternative for the management of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 174 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…Finally, the efficiency of cholesterol efflux induced by sequential administration of antagomiR‐33a by DPPC:CE:LPC rHDL followed by DPPC rHDL was evaluated in macrophage‐derived foam cells loaded with TopFluor Cholesterol ( Figure A). [ 56 ] The efficiency of DPPC rHDL as cholesterol acceptor was compared with natural HDL (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the efficiency of cholesterol efflux induced by sequential administration of antagomiR‐33a by DPPC:CE:LPC rHDL followed by DPPC rHDL was evaluated in macrophage‐derived foam cells loaded with TopFluor Cholesterol ( Figure A). [ 56 ] The efficiency of DPPC rHDL as cholesterol acceptor was compared with natural HDL (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, a large number of studies have used rHDL as therapeutic agent addressing the central antiatherogenic and cardioprotective properties of HDL. [56,82] Inflammatory and atherogenic processes have been shown to be reduced by repeated infusion treatment with rHDL. [83] Therefore, sequential administration of antagomiR-33a-loaded rHDL followed by DPPC rHDL infusion could represent a good strategy to favor the reverse transport of cholesterol and contribute to the reduction of atheroma plaque.…”
Section: Discussionmentioning
confidence: 99%
“…High‐density lipoprotein (HDL) is a nanoparticle with a diameter of ≈10 nm and antiatherogenic properties; [ 6 ] its nascent form has been reconstituted with recombinant apolipoprotein A‐I and phosphatidylcholine. [ 7 ] We previously reported that a library of the engineered nascent forms with different CPPs, phospholipids, and sizes were screened for the efficiency of posterior drug delivery via eye‐drop instillation, and the form with the best efficiency provided therapeutic efficacy in a mouse model of neovascular AMD. [ 8 ] Importantly, therapeutic efficacy was observed for both drug cargo and HDL variant.…”
Section: Introductionmentioning
confidence: 99%
“…Discoidal high-density lipoprotein (HDL) is characterized by the association of amphiphilic apoproteins (apoA-I) to phospholipid membrane discs with a size of approximately 10 nm, which can be easily reconstituted in vitro . Recent research has shown that synthetic HDL functions as a drug nanocarrier because of its small size, amphiphilic nature, and biocompatibility. In previous research, we produced an HDL variant containing an amphiphilic cationic peptide penetratin and 1,2-distearoyl- sn -glycero-3-phosphocholine (DSPC), designated as engineered lipoprotein 1 (eLP1), and a drug–eLP1 complex eye drop was instilled in a mouse model of age-related macular degeneration to demonstrate significant therapeutic efficacy . Importantly, the efficacy of the eLP1 formulation was greater than that of the liposomal formulation.…”
mentioning
confidence: 99%